AVIFAUNA DIVERSITY OF AMARKANTAK, MP (INDIA) - RANI, REKHA; MARKO, RAVIKANT (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Amarkantak is a holy place according to the Hindu religion. It is the origin place of the Narmada River; local people call it “Maa Narmada” with great respect. The tropical deciduous forest of Amarkantak is the natural habitat of many birds; there are dams, agriculture fields, and grassland, which are the best spots for bird watching. During fieldwork, it has identified 85 species of birds belonging to 15 orders and 48 families in 6 different areas- Jamunadhadar, Kapilasangam, Sonmuda, Mai ki bagiya, Main mandir, and Chakrathirth, from 7 February 2021 to 12 March 2021. In this study morning and evening hours of each day has selected to identification and observation in different spots like dam, agriculture field, grassland, and forest area of sites. Jamunadhadar has the richest avian fauna diversity with 60 species, followed by Chakratirth having 54 species, then Sonmuda having 39 species and the least number of avian fauna recorded was 11 at Main Mandir. In Jamunadhaar; Dam, agriculture field, small ponds and grass- lands serve as a better habitat for different type of birds. Spotted creeper (Salpornis spilotus) sighted at Jamunadhader and Sonmuda. It was not recorded in previous year survey of Achanakmar-Amarkantak Biosphere Reserve. Red naped Ibis (Pseudibis papillosa) is another bird which was not sighted in Amarkantak in previous survey, this bird in Jamunadhader and Chakratirth and Kapilasangam has seen in this study.